STRATEGIC MULTICRITERIA DECISION-MAKING PROCESS IN AGRICULTURE - Bogdanović, Strahinja; Hadžić, Miroljub (Economics of Agriculture, 2019)
The annual plantations in agriculture do not require large investments; therefore financial yields with this type of investments are limited. On the other hand, investment in perennial plantations, such as walnuts, hazelnuts or apples can be significantly higher, but the ROI or the return on such investment is therefore much higher than those on classic crop production. Making complex strategic decisions in agriculture, like whether to invest in an annual or move to perennial plantations, has been out of the sight for economic theorists for a long time. Therefore, the scientific contribution of this article is an effective use of a hybrid model that combines a quantitative method – such as the Net Present Value (NPV), and a qualitative method - such as the Analytical Hierarchy Process (AHP) in a multi criteria decision-making environment which proved that choosing the perennial plantations is a better long term investment strategy then the classic crop production.